‘The White Bones Were Collected and Inserted in a Golden Urn’ (Il. 24,793): Notes on Symbology of the Cinerary in the Ancient World - Lepore, Giuseppe (Eikón / Imago, 2020)
This paper attempts to retrace the reasons for the choice of the container gathering the burnt remains after the practice of incineration. Indeed, the voluntary destruction of the body is an ancient and highly symbolic practice, which has not been sufficiently investigated so far in a broad perspective (even from a chronological point of view) and with a multidisciplinary approach. The starting point for the exposed remarks is the excavation with related recent publication of a Hellenistic necropolis in Epirus (Phoinike). From this privileged observatory, supported by detailed anthropological investigations, a fascinating itinerary will be attempted, moving across the Greek world, up to the threshold of the Roman times, between myths and rites connected to fire.